PERBANDINGAN INDEKS MASSA TUBUH DAN TEKANAN DARAH PADA PEKERJA DI RUMAH POTONG HEWAN DAN KELOMPOK PETANI DI KOTA KENDARI - Dionisius Excelsis Deo Sombolinggi; Andi Noor Kholidha Syarifin; Tien Tien; Laode Kardin; Pranita Aritrina; Arimaswati Arimaswati (NHM PRESS, 2022)
Circadian rhythm is a natural clock in the human body. Night work can cause disturbances in the circadian rhythm. Circadian rhythm disturbances are known to be associated with an increase in psychosocial stress which can lead to an increase in blood pressure and BMI. This study aimed to compare BMI and blood pressure in day and night workers. This study was an analytical observational methods with a design case control. It was conducted in Labibia Village, Mandonga District and Anggoya Slaughterhouse, Kendari City in November 2021. The number of samples is 65 respondents, consist of 20 slaughterhouse workers and 45 farmer groups. Data analysis was carried out with the statistical test Chi-Square and then continued by determining the Odds Ratio (OR). The results showed that there was no significant difference between BMI of slaughterhouse workers and farmer groups (p = 0,096; POR 2,471 95% CI 0,840 – 7,265) and there was a significant difference between blood pressure of workers in abattoirs and farmer groups (p = 0,000 ; POR 52,250 ; 95% CI 6,293 – 433,842). There was no significant difference between BMI in slaughterhouse workers and farmer groups in Kendari city. There was a significant difference between blood pressure in abattoir workers and farmer groups in Kendari city in 2021 and night work was a risk factor for increasing blood pressure.